2018
DOI: 10.1080/15384101.2018.1557488
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Fbxo6 inactivates spindle checkpoint by interacting with Mad2 and BubR1

Abstract: The spindle assembly checkpoint prevents chromosome mis-segregation during mitosis by delaying sister chromatid separation. Several F-box protein members play critical roles in maintaining genome stability and regulating cell cycle progress via ubiquitin-mediated protein degradation. Here, we showed that Fbxo6 critically regulated spindle checkpoint and chromosome segregation. Fbxo6 was phosphorylated during mitosis. Overexpression of Fbxo6 lead to faster exit from nocodazole-induced mitosis arrest through pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…FBXO6 has been reported to target DNA damage checkpoint kinase Chk1 for destruction to the arrest cells at the S phase and plays a role in chemotherapy resistance 15 . Consistent with the role of FBXO6 in cell cycle control, we also found that FBXO6 is a cell cycle-specific phosphorylated protein, which is phosphorylated during mitosis and dephosphorylated after the cell enters the G1 phase 16 . FBXO6 can bind to Mad2 and BubR1 proteins to inactivate the spindle checkpoint, indicating that FBXO6 might have a function similar to tumor-promoting genes 16 .…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…FBXO6 has been reported to target DNA damage checkpoint kinase Chk1 for destruction to the arrest cells at the S phase and plays a role in chemotherapy resistance 15 . Consistent with the role of FBXO6 in cell cycle control, we also found that FBXO6 is a cell cycle-specific phosphorylated protein, which is phosphorylated during mitosis and dephosphorylated after the cell enters the G1 phase 16 . FBXO6 can bind to Mad2 and BubR1 proteins to inactivate the spindle checkpoint, indicating that FBXO6 might have a function similar to tumor-promoting genes 16 .…”
Section: Introductionsupporting
confidence: 86%
“…Consistent with the role of FBXO6 in cell cycle control, we also found that FBXO6 is a cell cycle-specific phosphorylated protein, which is phosphorylated during mitosis and dephosphorylated after the cell enters the G1 phase 16 . FBXO6 can bind to Mad2 and BubR1 proteins to inactivate the spindle checkpoint, indicating that FBXO6 might have a function similar to tumor-promoting genes 16 . It is worth noting that FBXO6 can recognize glycosylated proteins through its FBA domain and participate in the regulation of endoplasmic reticulum-related glycoprotein degradation 17 .…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Fbxo6 is a member of F-box family which serves as a mediator in targeting bound target proteins for ubiquitination and destruction [1,17]. In the previous studies, Fbxo6 was found interacting with multiple molecules and regulated cellular sensitivity to replication stress [5][6][7][8][9]. Since the existed literature has demonstrated that there was a close relationship between the metabolic system of ubiquitin and the proliferation and apoptosis of human cancer, we hypothesized that Fbxo6 also played a role in both unperturbed and cisplatin-pretreated NSCLC cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…The F-box proteins mediate the function of ubiquitination of SCF E3 ligase complex by interacting with distinct sets of ubiquitin acceptor proteins [3,4]. Previous studies have demonstrated that impaired Fbxo6 expression promoted the therapeutic resistance of human cancer cells by inducing the ubiquitin-mediated degradation of multiple target molecules [5][6][7][8]. Zhang et al [9] found that Fbxo6 facilitated the ubiquitination and degradation of Chk1 by directly binding with it.…”
mentioning
confidence: 99%